Strategy Deployment and Spotify Rhythm - Scotl, Karl (2016)
Last month, Henrik Kniberg posted slides from a talk he gave at Agile Sverige on something called Spotify Rhythm - "Spotify’s current approa ch to getting aligned as a company". While looking through the materia l, it struck me that what he was describing was a form of Strategy Dep loyment. This interpretation is based purely on those slides - I haven 't had a chance yet to explore this more deeply with Henrik or anyone else from Spotify. I hope I will do some day, but given that caveat, h ere's how I currently understand the approach in terms of the X-Matrix Model.